Periphrastic Causativization in Toba from Eastern and Western Formosa province (Argentina) - González, Raúl Eduardo; Carpio, María Belén (Íkala, Revista de Lenguaje y Cultura, 2017)
The aim of this paper is to analyze, from the functionalist perspective, periphrastic causative constructions in Toba from Eastern and Western Formosa province and comparatively between the two varieties. The degree of fusion of the cause and effect predicate, their order, and paradigmatic variability are the features studied. The periphrastic causative constructions in Toba from Eastern Formosa described was not previously detected in the mutually intelligible varieties from the Chaco province. Besides, it is shown that this construction differs, especially in terms of the degree of grammaticalization, from the periphrastic construction in Toba from Western Formosa. The corpus is composed of oral texts and elicited clauses collected during fieldwork pursued in three communities: Vaca Perdida in Western Formosa, and Nam Qom neighborhood and Bartolomé de las Casas in Eastern and Middle-eastern Formosa. This paper is a contribution to comparative studies of periphrastic causative constructions of two varieties of Toba. In the absence of diachronic sources, the synchronic comparison of genetically related languages, but spoken by ethonohistorically different peoples, provides empirical evidence to hypothetically postulate grammaticalization processes in course.